Perancangan User Experience Aplikasi Crowdfunding Pariwisata Desa menggunakan Metode Design Thinking (Studi Kasus: Pariwisata Desa Jembul Kabupaten Mojokerto) - Putri Nur Utami Ramadhani; Satrio Hadi Wijoyo; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Department of Youth and Sports Tourism of Mojokerto Regency is the implementing element of government affairs that oversees tourism and includes village tourism in it. The problem experienced in the management of tourism in Mojokerto district lies in the income of village tourism funds so that the exploration of village tourism potential cannot be maximized. Based on the Mojokerto Regency Regional Regulation (PERDA) number 8 of 2019 it can be seen that one of the master plans for tourism development in Mojokerto Regency in 2018-2033 is to increase community empowerment in developing tourism potential. Therefore, it is necessary to design a crowdfunding application user experience to improve village management independently by involving the active role of the community used by tourism village managers, especially tourism in Jembul village and other tourism locations in the Mojokerto. The design method used is Design Thinking which has five stages, namely; empathize, define, ideate, prototyping, and testing. This research produces a high-fidelity prototype. Tests and assessments in this study used the User Experience Questionnaire (UEQ) with the test results on attractiveness having an average value of 2.07, perspicuity having an average value of 1.9, efficiency having an average value of 1.8, dependability has an average value of 2.06, stimulation has an average value of 2.09, and novelty has an average value of 2.18.